Significantly shortened telomere length and altered androgen receptor level in cumulus cells from women with polycystic ovary syndrome - Tzu-Ning Yu; En-Hui Cheng; Yi-Ping Lin; Yi-Chun Chen; Chun-Chia Huang; Tsung-Hsien Lee; Maw-Sheng Lee (Elsevier, 2023)
Objective: The aim of this study was to investigate the correlation between hormone receptor levels and telomere length (TL) in infertile women with and without polycystic ovary syndrome (PCOS). Materials and methods: This prospective cohort study recruited a total of 431 cumulus oocyte complex (COC) from 88 infertile women between July 2012 and June 2014. The participants were divided into three groups: young age (<38 years, n = 42 and 227 COC), advanced age (≥38 years, n = 33 and 107 COC) and PCOS patients (n = 13 and 97 COC). Cumulus cells were collected from individual follicle during oocyte pick-up, and the mRNA levels of hormone receptors and TL were measured using real-time PCR. Results: The cumulus cells of PCOS patients demonstrated lower mRNA levels of LH receptor (75.57 ± 138.10 vs. 171.07 ± 317.68; p < 0.01) and androgen receptor (1.13 ± 1.52 vs. 4.08 ± 9.57; p < 0.01), as well as a shorter TL (2.39 ± 2.58 vs. 3.96 ± 4.72; p < 0.01) compared to those of the young age group. In the young age group, only androgen receptor mRNA level showed a significant association with TL (rho = 0.148, p = 0.026), while FSH receptor mRNA level was the only factor associated with TL (rho = 0.247, p = 0.015) in PCOS patients. For advanced-aged patients, no significant relationship was observed between hormone receptor mRNA levels and TL. Alternative splicing of androgen receptors was identified in some PCOS patients but not in young age controls. Conclusion: The findings suggest that the androgen receptor level and function may be altered in the cumulus cells of PCOS patients, leading to a shorter TL in cumulus cells in PCOS patients.